Electrocatalytic Production of Hydrogen‐peroxide from Molecular Oxygen by Rare Earth (Pr, Nd, Sm or Gd) Oxide Nanorods. Issue 11 (13th August 2020) - Hota, Ipsha; Debnath, A. K; Muthe, K. P; Varadwaj, K. S. K; Parhi, Purnendu
Abstract: Highly selective two electron oxygen reduction pathway to generate hydrogen peroxide using four different rare earth (Pr, Nd, Sm, Gd) oxides has been studied. From the rotating‐ring‐disc electrochemical experimental observations, it can be concluded that among the four rare earth oxides, Gd2 O3 shows higher ring current and can efficiently produce H2 O2 (yield of HO2 − =80 %) following 2 electron (number of electrons involved in the process was calculated as 2.2) pathway in 0.1 M KOH. The selectivity for H2 O2 was improved by the synergistic coexistence of volcano carbon (VC) with rare‐earth oxides, while Nd2 O3 mixed with VC ink showed maximum (91.91 %) selectivity for the H2 O2 production. The electrochemical active surface area calculated by measuring the charging current of the electric double layer is compared. The ORR kinetics of the synthesized catalysts were studied by comparing the rate constants and tafel slopes at selected potential ranges. Abstract :